2012
DOI: 10.1523/jneurosci.0515-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Microsaccadic Efficacy and Contribution to Foveal and Peripheral Vision

Abstract: Our eyes move constantly, even when we try to fixate our gaze. Fixational eye movements prevent and restore visual loss during fixation, yet the relative impact of each type of fixational eye movement remains controversial. For over five decades, the debate has focused on microsaccades, the fastest and largest fixational eye movements. Some recent studies have concluded that microsaccades counteract visual fading during fixation. Other studies have disputed this idea, contending that microsaccades play no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
141
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(156 citation statements)
references
References 54 publications
(122 reference statements)
14
141
1
Order By: Relevance
“…However, studies on image fading commonly use low-frequency stimuli, and the global reduction in contrast sensitivity measured under prolonged retinal stabilization is more pronounced at low spatial frequencies. It has been recently observed that visibility of a 0.2 cycles/deg is enhanced by saccades larger than 30′, but that smaller saccades only have a very modest effect (McCamy et al, 2012). These previous results are in agreement with the findings of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on image fading commonly use low-frequency stimuli, and the global reduction in contrast sensitivity measured under prolonged retinal stabilization is more pronounced at low spatial frequencies. It has been recently observed that visibility of a 0.2 cycles/deg is enhanced by saccades larger than 30′, but that smaller saccades only have a very modest effect (McCamy et al, 2012). These previous results are in agreement with the findings of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A saccade was identified when the eye-movement velocity exceeded this threshold for 7 ms (7 consecutive eye-position samples). We also imposed a minimum intersaccadic interval (defined as the interval between the last sample of one saccade and the first sample of the next saccade) of 10 ms so that potential overshoot corrections were not considered new fixational saccades (McCamy et al, 2012; Møller, Laursen, Tygesen, & Sjølie, 2002). Eye velocity during blink intervals was ignored when calculating the threshold.…”
Section: Methodsmentioning
confidence: 99%
“…It has long been suggested that microsaccades serve a special role in preventing perceptual fading [8, 33], but this popular hypothesis has remained controversial among researchers [1, 31, 32, 34, 35, 36], and visual impairments similar to those occurring with larger saccades have been observed at the time of microsaccades [37, 38, 39, 40]. Recent studies have shown that when observers are not required to maintain fixation—an unnatural laboratory condition—but are left free to normally move their eyes, microsaccades precisely shift gaze toward nearby interesting locations [41].…”
Section: Types Of Fixational Eye Movementsmentioning
confidence: 99%